Capacitor multiplier with high multiplication factor for integrated low pass filter of biomedical applications using DTMOS technique - Alaybeyoğlu, Ersin; Kuntman, Hakan; Alaybeyoğlu, Ersin (Elsevier Gmbh, 2019)
In this work, capacitor multiplier circuit is designed for use in biomedical applications. The designed circuit operates with +/- 0.3 V supply voltage at very low quiescent current. The design of the proposed circuit is realized with DTMOS technique by using standard CMOS process. The designed circuit has a high multiplication factor and allows the integration of the capacitance of the low-pass filters required in low-frequency applications such as bio-medicals. At the same time, the proposed circuit has the low power consumption that should be in implantable devices. The proposed circuit is designed with 0.18 mu m TSMC technology in Cadence environment. (C) 2019 Elsevier GmbH. All rights reserved.
Keywords: Capacitance Multiplier; Bio-Medical Applications; Operational Transconductance Amplifier (Ota)